India at the global high table : the quest for regional primacy and strategic autonomy - Schaffer, Teresita C.; Schaffer, Howard B. (Washington, D.C. : Brookings Institution Press, 2016)
"In recent decades, India has grown as a global power, and has been able to pursue its own goals in its own way. Negotiating for India's Global Role gives an insightful and integrated analysis of India's ability to manage its evolving role. Former ambassadors Teresita and Howard Schaffer shine a light on the country's strategic vision, foreign policy, and the negotiating behavior that links the two. The four concepts woven throughout the book offer an exploration of India today: its exceptionalism; nonalignment and the drive for "strategic autonomy;" determination to maintain regional primacy; and, more recently, its surging economy. With a specific focus on India's stellar negotiating practice, Negotiating for India's Global Role is a unique, comprehensive understanding of India as an emerging international power player, and the choices it will face between its classic view of strategic autonomy and the desirability of finding partners in the fast-evolving world"--
Includes bibliographical references and index.
Keywords: POLITICAL SCIENCE / International Relations / Diplomacy; BUSINESS & ECONOMICS / International / Economics; India -- Foreign relations -- 21st century